Strain-tunable molecular doping in germanane: a first-principles study. (21st September 2018) - Wang, X; Liu, G; Liu, R F; Luo, W W; Wu, M S; Sun, B Z; Lei, X L; Ouyang, C Y; Xu, B
Abstract: Germanane, fully hydrogenated germanene, has recently attracted great interest, both theoretical and experimental. In this paper we thoroughly study strain-tunable n/p-type doping in germanane by adsorption of tetrathiafulvalene (TTF)/tetracyanoquinodimethane (TCNQ) molecules through first-principles calculations. The results show that both TTF and TCNQ molecules can non-covalently functionalize the electronic properties of germanane. Not surprisingly, TTF molecular adsorption induces n-type doping in germanane because the TTF molecule is a typical electron donor. Moreover, a linearly tunable band gap of germanane and differing n-type doping strengths can be realized by a biaxial strain ranging from −3% to 3%. Analysis indicates that tensile strain would promote the doping effect whereas compressive strain would inhibit it. Comparatively, TCNQ molecular adsorption induces a germanane/TCNQ system which exhibits metallic characteristics. Surprisingly, however, under a tensile strain of 2.5%, a strong p-type doping effect is achieved in germanene/TCNQ. In particular, with increasing tensile strain over the range 2.5%–3%, the strain-tunable p-type doping effect decreases gradually. Such a multiple effect of molecular adsorption and strain on the electronic properties of germanane could be helpful for potential future applications of germanane-based electron devices.